Corporate social responsibility in maritime transport : a contingency framework - Yuen, Kum Fai (2017)
Corporate social responsibility (CSR) involves the integration of social and environment concerns into business activities and processes. CSR has received growing attention from the maritime transport sector in view of rising competition and tightening of social and environmental regulations. However, the business case of CSR remains debatable. While some studies view CSR as a dilution of a firm’s core competitive advantage, others view CSR as an intangible resource that garners support and allegiance from stakeholders. The aim of this thesis is to analyse the relationship between corporate social responsibility (CSR) and business performance through the lens of contingency theory. Contingency theory asserts that situations influence the direction and magnitude of a relationship. A multi-level approach, consisting of internal, external, and dynamic level, was adopted to test this theory. Semi-structured interviews and a pilot test were conducted. Subsequently, primary data were collected using an online survey that was administered to the populations of shipping firms and shippers located in Singapore. Depending on the hypotheses, the obtained data were analysed using various statistical methods including factor analysis, interaction regression analysis, structural equation modelling, nested-model comparison, and multi-sampling approach. At the internal (intra-firm) level, it was found that the financial benefits of CSR are contingent on the primary competitive strategy of a shipping firm. There are greater benefits for shipping firms employing differentiation strategy (rather than low cost strategy) to implement CSR by virtue of greater mass in existing complementary resources (operational fit) as well as inherent congruency with customers’ value orientation (customer fit). At the external (environmental) level, the results show that the relationship between a shipping firm’s involvement in CSR and shippers’ willingness to pay for CSR is mediated by or contingent on factors such as customer satisfaction, customer loyalty, and shippers’ CSR beliefs. At the dynamic level, it was found that the financial benefits of CSR are contingent on shipping firms’ continuous improvement capacities, which are related to their learning and absorptive capacities. In addition, adopting a relatively gradual and regular pace in implementing continuous improvement programmes augments the effect of CSR on business performance. Overall, the findings reinforce contingency theory and provide a differentiated view of the relationship between CSR and performance. This differentiated view aligns with path dependence theory, theory of planned behaviour, and organisational learning theory which were used as anchors to reinforce the case of contingency at the internal, external, and dynamic level accordingly. The results also imply that CSR is not a one-size-fit-all strategy. Herein, maritime transport managers should evaluate the fit of their firms’ internal resources, external environment, and dynamic capabilities with respect to CSR prior to its implementation.